Influence of the alloying elements on the tribological performance of DLC coatings in different sliding conditions - Evaristo, Manuel (2023)
Reduction of friction and wear at the sliding surfaces are the main concern in several applications. From an extensive list of low friction hard coatings, DLC type is one of the most studied and develop for achieving low wear and friction. The addition of an alloying element is extensively used, since it can change significantly the coatings performance. Therefore, in this research the tribological behaviour of DLC coatings alloyed with different elements was evaluated, since no works comparing the tribological properties of DLC films with approximately the same alloying elements concentration are reported in the literature. The coatings were deposited by physical vapor deposition and alloyed with: tungsten (W), silver (Ag), silicon (Si), silicon and oxygen (SiO), with concentrations of metallic elements between 10 and 15 at. % and a pure DLC coating was also deposited for comparison purposes. The coatings hardness varied between 23 GPa for the pure DLC and 11 GPa for the alloyed with Si and O. The tribological behaviour of the coatings was evaluated by pin-on-disk against 10 mm 100Cr6 steel balls, at room temperature (RT) and 100 ◦C. The best wear resistance was achieved with the pure DLC and DLC-W for RT tests. At RT the lowest friction was obtained with the DLCSi and DLCSiO coatings. Despite of the low COF values, those coatings displayed the highest specific wear rate values among all the films. This is attributed to the presence of hard SiC particles stick at the ball counterpart which promotes severe abrasion of the coatings surface. The increase of the temperature to 100 ◦C increases significantly the friction coefficient for the DLC and DLC-W coatings, whilst, for DLC-Ag, DLC-Si and DLC-SiO coatings a slight decrease is noticed. At this temperature DLCAg coating is the more performing due to the formation of a tick tribolayer rich in Ag adhered at the counterpart surface. With this work it was concluded that friction and wear are not directly related, and the third bodies formed on the sliding surfaces have major influence on the tribological performance of the system.